GENETIC CHARACTERIZATION OF DWARF SNAKEHEAD, Channa gachua (Hamilton, 1822), FROM TWO POPULATIONS BASED ON 16S rRNA GENE - Ragil Pinasti; Warisatul Ilmi; Tuty Ari Suryani (Indonesian Fisheries Research Journal, 2021)
Indonesia is one of the countries with high biodiversity of freshwater fishes. One freshwater fish with a wide distribution in Asia with high economic potency for ornamental fish is dwarf snakehead. However, research on genetic characterization of dwarf snakehead from Indonesia is very limited. Therefore, this research aimed to compare genetic characterization of the dwarf snakehead from rice field irrigation at Donomulyo Village (Malang, East Java) and from Keji River (Magelang, Central Java). This study used a PCR method with universal primers: 16Sar and 16Sbr. The data obtained in this study were then analyzed using DNASTAR, BLAST, Mesquite, MEGA, DnaSP, and NETWORK. The results revealed the genetic distance between dwarf snakehead from rice field irrigation at Donomulyo Village and from Keji River was 1.36%. The divergence of GC content, haplotype number, variables sites, haplotype diversity, and nucleotide diversity in both populations exist. The results of this study are expected to arrange 16S mitochondrial DNA Library of dwarf snakehead from Indonesia which is useful for a reference in the conservation and utilization and management of dwarf snakehead in their habitat.